Satisfying Safety Goals by Probabilistic Risk Assessment - Kumamoto, Hiromitsu (Springer Series in Reliability Engineering,, 2007)
Safety is one of the most important issues today. Recent international standards such as ISO and IEC have consistently advocated goal-based procedures of designing systems for better safety. The procedure assumes safety goals are explicitly established by international organizations, individual nations, particular industries or private companies. Satisfying Safety Goals by Probabilistic Risk Assessment is a methodological approach to the goal-based safety design procedure that will soon be an international requirement. Satisfying Safety Goals by Probabilistic Risk Assessment primarily focuses on the quantitative aspects of international standards. The methodologies presented are illustrated through the use of case studies. The book also: presents accident statistics and safety goals; describes abnormal event enumeration for the target system; develops risk reduction mechanisms; discusses probabilistic risk assessment (PRA) models typified by event trees coupled with fault trees; presents conventional materials for basic event quantification; describes how to calculate safety criteria from the PRA models, given basic event data; evaluates uncertainties of point estimates of safety criteria; and considers how external event quantification can expand the scope of PRA. Satisfying Safety Goals by Probabilistic Risk Assessment will be a good reference for senior undergraduates, postgraduates and researchers in the fields of reliability engineering and safety engineering and risk assessment. It will also be of interest to reliability engineers, practitioners in industry and regulatory authorities. Dr Hiromitsu Kumamoto is a Professor in the Department of Systems Science at Kyoto University in Japan. His research interests include human roles in systems, human-machine systems, intelligent transport systems, and system reliability and safety assessment. Springer Series in Reliability Engineering publishes high-quality books in important areas of current theoretical research and development in reliability, and in areas that bridge the gap between theory and application in areas of interest to practitioners in industry, laboratories, business, and government.